Introducing forensic and criminal investigation - Monckton-Smith, Jane; Adams, Tony; Hart, Adam G; Webb, Julia (SAGE, 2013)
By introducing each step taken in a criminal investigation, this text allows students to gain a clear understanding of the processes involved and helps them to critically assess the interplay of investigations, criminology and forensics.